Patient approach in advanced/metastatic renal cell carcinoma: focus on the elderly population and treatment-related toxicity. (November 2013) - Verzoni, Elena; de Braud, Filippo; Fabiani, Francesca; Grassi, Paolo; Testa, Isabella; Procopio, Giuseppe
Recent therapeutic advances have changed the treatment landscape of metastatic renal cell carcinoma. Unfortunately, the seven agents now available are not based on biomarkers that would indicate which one could provide the best benefit for every patient. We have reviewed the available information concerning the impact of each treatment on comorbidities or status that are frequently seen before commencing treatment for the advanced disease: elderly and patients with cardiovascular complications, metabolic and endocrinology disorders, and infections, as well as impaired organ function (kidney, liver and heart). Additional new drugs will be launched, but no predictive biomarkers are available. Head-to-head studies to evaluate the safety of the different drugs are rare. In this quite complex scenario, we believe that a decision-making approach focused on the patient may represent a suitable strategy.